Seeds germination of different species in saline water (Research, Society and Development, 2022)
The objective of the work was to evaluate the interference of saline water in seeds germination of several species of economic interest. The experiment was developed at the Laboratory of Support to Teaching, Research and Extension of the Experimental Farm of Agricultural Sciences, Grand Dourados Federal University, in the municipality of Dourados, Mato Grosso do Sul state, Brazil. The germination tests were performed separately for each species, thus, each one has a methodology determined by Rules for Seed Analysis. The species used were: cotton, chickpea, pea, safflower, sesame, soybeans, and vetch. The treatments were formed by sodium chloride (NaCl) dissolved in water: T1 – control (0.0 g L-1 – 0.065 mS cm-1); T2 – 3.0 g L-1 (5.50 mS cm-1 ); T3 – 6.0 g L-1 (10.70 mS cm-1) and T4 – 9.0 g L-1 (15.10 mS cm-1). All treatments were cultivated in B.O.D with constant light and temperatures according to the species. The characteristics evaluated were: First count; percentage of germination; germination speed index; mean germination time; mean germination speed and seedling length. The experimental design used was completely randomized with four treatments and four replications. Doses up to 6.0 g L-1 of NaCl had not interfered on germination of cotton, chickpea, safflower and sesame seeds. Pea, soybean and vetch have not had their germination influenced by concentrations of NaCl used. Water salinity may not harm germination, however, it affects seedlings growth, and may be a determining factor in achieving the ideal population of each crop at field level.